Association between non-traditional lipid parameters and futile recanalization in patients with acute ischemic stroke undergoing mechanical thrombectomy - Jia Duan; Jian Duan; Longyi Zheng; Shuang Tang; Shuang Xie; Wenli Xing; Ao Qian (European Journal of Medical Research)
Abstract Background Non-traditional lipid parameters are crucial biomarkers associated with outcomes of acute ischemic stroke (AIS). We aim to explore the relationship between non-traditional lipid parameters and futile recanalization (FR) following mechanical thrombectomy (MT) for acute large artery occlusion (LAO). Methods A retrospective study was conducted in our stroke center. The definition of FR is modified Rankin scale (mRS) score ≥ 3 at 90-day follow-up. The non-traditional lipid parameters include atherogenic index of plasma (AIP), apolipoprotein (Apo) B/A1 ratio, Castelli’s risk index (CRI), lipoprotein combine index (LCI), residual lipoprotein cholesterol (RLP-C), and non-high-density lipoprotein cholesterol (non-HDL-C). Multivariate regression analysis was performed to identify independent factors of FR between these parameters, as continuous variables. Then, AIP, Apo B/A1 ratio, CRI-I, and CRI-II, all of which met the significance, were categorized into tertiles to further investigate their relationship with FR through multivariate regression analysis and restricted cubic spline (RCS) curves. Then, linear regression analysis was employed to explore the association between non-traditional lipid parameters and the final infarct volume. Results A total of 338 patients were enrolled into this study, and 196 (56.5%) patients experienced FR. AIP, Apo B/A1 ratio, CRI-I, and CRI-II were categorized into tertiles based on value. Compared with patients in the lowest tertile, those in the highest tertile had significantly increased risk of FR (AIP: odds ration [OR] 2.64, 95% CI 1.27–5.51, P = 0.009; Apo B/A1 ratio: OR 2.21, 95% CI 1.12–4.40, P = 0.023; CRI-I: OR 3.41, 95% CI 1.60–7.31, P = 0.002; CRI-II: OR 3.38, 95% CI 1.58–7.21, P = 0.002). RCS curves demonstrated a linear relationship between those four parameters and FR (all P non-linear > 0.05). Linear regression analysis confirmed that AIP and CRI-II were positively correlated with the final infarct volume (AIP: β 2.61, 95% CI 0.20–5.03, P = 0.034; CRI-II: β 8.93, 95% CI 1.12–16.74, P = 0.025). Conclusion This study provides evidence that AIP, Apo B/A1, CRI-I, and CRI-II are independent risk factors of FR following MT for acute LAO, and can be novel biomarkers of prognosis in patients treated with MT.